Cost & Time Interaction Behavior on Construction Materials Procurement and Execution Processes in Infrastructure Projects - Aktham Kh. Majeed; Kadhim Raheim Erzaij (Salehan Institute of Higher Education, 2020)
The cost of construction materials forms a large proportion of the total cost of construction projects Thus, the lack of a sound time and cost management planning for construction materials procurement will lead to deficiencies in the supply and flow of construction materials, not to mention its negative consequences of delays and financial losses which are often cited as major causes of product degradation. This research will present the development of an applicable procurement management system model particularly for UPVC & Ductile pipes used in water and sewage water infrastructure Projects in Iraq. Actual data are collected from seven Iraqi infrastructure projects. These data are analyzed by using SBSS v. 23 statistical analysis programs. On the bases of analyses results, four mathematical relationships have been developed by using MATLAB R2015B & CurveExpert Basic software to be used on building a realistic procurement management system with accurate, acceptable, and appropriate results for the construction materials procurement conditions in Iraq, the system was finally tested by using actual data from Al-Latifiyia sewer project in Baghdad governorate, where the system showed an accuracy results of 86%.